1993
DOI: 10.1007/bf00016337
|View full text |Cite
|
Sign up to set email alerts
|

Variability in nitrogen fixation of common bean (Phaseolus vulgaris L.) intercropped with maize

Abstract: Thirty one selected bean lines were evaluated in the field for ability to support N 2 fixation when intercropped with maize which received 0, 30 and 60 kg N ha-I as ammonium sulphate. The amount of fixed N 2 was estimated using the natural variation of ~5N and wheat as the standard non-fixing crop. Nitrogen as low as 15 kg N ha -1 at sowing suppressed nodule weight and activity (acetylene reduction activity) but not nodule number, suggesting that the main effect of mineral N was on nodule development and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
4
18
2
Order By: Relevance
“…The highest biomass and grain production in all experimental locations was also recorded with Gofta. This finding is consistent with the observation of Tsai et al (1993) who found that Mexico-309 was superior for nodulation parameters but poor for seed yield, while Preto Caruaru produced high seed yield, but was inferior in nodulation traits. The yield advantage of Gofta could be attributed to its delayed maturity when compared to other tested common bean genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…The highest biomass and grain production in all experimental locations was also recorded with Gofta. This finding is consistent with the observation of Tsai et al (1993) who found that Mexico-309 was superior for nodulation parameters but poor for seed yield, while Preto Caruaru produced high seed yield, but was inferior in nodulation traits. The yield advantage of Gofta could be attributed to its delayed maturity when compared to other tested common bean genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…The present study also indicated the positive effect of Rhizobium inoculation on AE-N at low rates of N application (i.e., less than 40 kg N ha enhances productivity and nodulation of common bean (Tsai et al 1993b;Daba and Haile 2000;Hungria et al 2003). At Babillae site, the highest AE-N (10.16 and 11.6 kg kg −1 ) from inoculated and uninoculated treatments was obtained at 40 and 20 kg N ha −1 , respectively.…”
Section: Resultssupporting
confidence: 71%
“…The result obtained in these three sites agreed with previously reported by Daba and Haile (2000) who found that starter N with Rhizobium inoculation recommended to improve nodulation and yield of common bean in eastern Ethiopia. The application of a small amount of fertilizer N (15-30 kg N ha −1 ) enhances nodulation of different legume crops (da Silva et al 1993;Tsai et al 1993b;Hungria et al 2003). The better performance of common bean in nodulation in inoculated treatments might be related with plant growth promoting activities of inoculated isolate, beside N 2 fixation (Atzorn et al 1988).…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed difference (P < 0.05) indicated that the nitrogen biological fixation potential activity was impaired by the presence of the nitrogen fertilizer. There is a close relation between nodule number and enzyme nitrogenase activity (Vincent, 1975;Tsai et al, 1993). Regarding the number of stems, nitrogen content, crude protein and non-protein nitrogen content, the cultivar Pioneer-5454, characterized by prostrated growth habit and dormancy degree 3, presented superior performance in comparison to the other cultivars, but showed lower dry matter production (Table 2).…”
Section: Biological N 2 Fixation and Nitrogen Fertilization Effects Omentioning
confidence: 99%